Village Cooperatives as Instruments for the Fulfillment of Economic, Social, and Cultural Rights: A Human Rights-Based Approach - Yusuf Eko Nahuddin; Riski Febria Nurita; Khotbatul Laila (Universitas Kristen Cipta Wacana, 2026)
This study examines the relevance of village cooperatives from a human rights perspective, particularly in fulfilling economic, social, and cultural rights (ESCR) in rural communities. Using a normative legal research method, this study analyzes statutory regulations, legal doctrines, and human rights principles at both national and international levels. The findings indicate that village cooperatives, as community-based economic institutions grounded in the principles of mutual cooperation and economic democracy, have strong potential to function as instruments for the realization of human rights. Village cooperatives contribute to the fulfillment of economic rights by providing access to capital, employment opportunities, and market participation, thereby improving community welfare and reducing poverty. In addition, they support social and cultural rights through the provision of basic services, strengthening social solidarity, and preserving local cultural values. However, the effectiveness of village cooperatives remains constrained by challenges such as limited managerial capacity, restricted access to resources, and the lack of integration of human rights principles into cooperative governance. This study emphasizes the importance of strengthening village cooperatives through a human rights-based approach by enhancing institutional capacity, improving policy support, and promoting active community participation. By doing so, village cooperatives can serve as strategic instruments for achieving inclusive, equitable, and sustainable rural development